PENGARUH NEGARA ASAL TERHADAP PERSEPSI KUALITAS - FITRIYAH, RENY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This study aims to analyze and discuss the influence of country of origin on the perceived quality. The study focused on the sharp brand for TV, AC, and washing machines. This research is conclusive. The population used was the visitors Hartono Elektronika Kertajaya Indah Timur Surabaya. Sample taken as many as 110 peoples with purposive sampling technique. Then the sample was divided into two groups of control and experimental group. The research instrument used was a questionnaire and the data obtained were processed using simple regression analysis, followed by analysis of independent samples t test. The results showed that there is significant influence between the country of origin of the perceived quality of the control group and experimental group. For the analysis of independent samples t test there was no difference effect to country of origin on perceived quality to experimental and control group. Keywords: country of origin and perceived quality.